Kualitas Pelayanan Publik Dalam Pembuatan Kartu Tanda Penduduk Elektronik (E-Ktp) Di Suku Dinas Kependudukan Dan Catatan Sipil Kota Jakarta Selatan - Tampang, Mesriani; Sartika, Ika; Ruhana, Faria (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2024)
Service uncertainty, such as the length of printing time and procedures for correcting E-KTP data, is still a serious problem and there is still a lack of updated information on online service procedures provided by the Department of Population and Civil Registration. E-KTP service procedures and problems with online services via the website of the Department of Population and Civil Affairs. South Jakarta City Civil Registration. This research aims to describe the quality of public services in making E-KTPs at the South Jakarta City Population and Civil Registry Department. This research contains 5 (five) dimensions which are the initial requirements for services built according to the theory of Zeithaml, Berry and Parasuraman in Hardiyansyah, namely Tangibles, Reliability, Responsiveness, Assurance, Empathy. This study used descriptive qualitative method. The data collection techniques used were observation interviews and documentation. The author uses data analysis techniques with stages of data reduction, data presentation, verification and conclusions are prepared tentatively. Based on the research conducted, it is known that the quality of public services in making E-KTPs at the South Jakarta City Population and Civil Registry Department has not gone well. The author still finds problems related to limited facilities and infrastructure, lack of availability of blanks, lack of officer discipline. Meanwhile, the author looks at the model used for the quality of public services in making E-KTP at the population and civil registration sub-department which is carried out using a mechanical model, an organic model.